Immunopharmacology in Vernal Keratoconjunctivitis: Current and Future Perspectives - DeGaulle I. Chigbu; Bisant A. Labib (MDPI AG, 2021)
Vernal keratoconjunctivitis (VKC) is a complex and chronic, multifactorial Th2 cell-mediated chronic ocular surface inflammatory condition that typically affects predominantly male children in hot or warm climates. The primary symptom is intense ocular pruritus, often significant enough to affect activities of daily living. Clinical features differ from simple forms of allergic conjunctivitis in that they are more-or-less confined to the superior tarsus and limbus. There is also a risk of corneal involvement, which leads to irreversible vision loss in approximately 6% of patients. Right now, there is no standardized treatment protocol, and many of the currently available options are not effective in severe and recurrent cases. As such, it is imperative to understand this complex allergic immune response in order to identify future therapeutic targets. This review will focus on potential drug targets in VKC, with particular emphasis on immunomodulators and immunobiologic agents.